2015
DOI: 10.7567/jjap.54.064101
|View full text |Cite
|
Sign up to set email alerts
|

Annealing influence on recovery of electrically stressed power vertical double-diffused metal oxide semiconductor transistors

Abstract: The effect of annealing on the recovery of electrically stressed power vertical double-diffused metal oxide semiconductor (VDMOS) transistors has been investigated. Behaviors of device threshold voltage and channel carrier mobility have been analyzed in terms of underlying changes in the densities of gate oxide charges and interface traps. The mechanisms responsible for the above-mentioned changes during the recovery of stressed devices have been analyzed as well. The annealing resulted in achieving stable thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It should be noted that the results regarding the SiO 2 and SiO 2 -Si interface published so far are of importance since they contribute to the process of determining the nature of the oxide and the interface defects. These defects were mostly responsible for the effects of irradiation, accelerated testing, high electric field stress (HEFS), and bias temperature (BT) stress, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] observed in power MOS transistors, as well. There is particular interest in research of reliability and effects induced by harsh conditions during operation of novel power vertical double-diffused MOS (VDMOS) transistors in different applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the results regarding the SiO 2 and SiO 2 -Si interface published so far are of importance since they contribute to the process of determining the nature of the oxide and the interface defects. These defects were mostly responsible for the effects of irradiation, accelerated testing, high electric field stress (HEFS), and bias temperature (BT) stress, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] observed in power MOS transistors, as well. There is particular interest in research of reliability and effects induced by harsh conditions during operation of novel power vertical double-diffused MOS (VDMOS) transistors in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…This interest has continuously risen during the last decades. [20][21][22][25][26][27][28][29][30][31][32][33][34][35][36][37] The results have shown that ionizing irradiation may reduce system lifetime that could be caused by degradation of several electrical parameters of power MOS transistors, especially threshold voltage (V T ) as the most important one. It should be noted that negative threshold voltage shift (ΔV T ) induced by radiation is the most critical reliability problem since it may cause change of operation mode from enhancement to depletion in n-channel power MOS transistors or dramatically reduction of current driving capability in p-channel ones.…”
Section: Introductionmentioning
confidence: 99%